2019
DOI: 10.1007/s00180-019-00933-8
|View full text |Cite
|
Sign up to set email alerts
|

Near G-optimal Tchakaloff designs

Abstract: We show that the notion of polynomial mesh (norming set), used to provide discretizations of a compact set nearly optimal for certain approximation theoretic purposes, can also be used to obtain finitely supported near G-optimal designs for polynomial regression. We approximate such designs by a standard multiplicative algorithm, followed by measure concentration via Caratheodory-Tchakaloff compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Following References [18,19], we can however effectively compute a design which has the same G-efficiency of u(k) but a support with a cardinality not exceeding N 2m = dim(P d 2m (X)), where in many applications N 2m card(X), obtaining a remarkable compression of the near optimal design. The theoretical foundation is a generalized version [15] of Tchakaloff Theorem [20] on positive quadratures, which asserts that for every measure on a compact set Ω ⊂ R d there exists an algebraic quadrature formula exact on P d n (Ω)), with positive weights, nodes in Ω and cardinality not exceeding N n = dim(P d n (Ω).…”
Section: Computing Near G-optimal Compressed Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following References [18,19], we can however effectively compute a design which has the same G-efficiency of u(k) but a support with a cardinality not exceeding N 2m = dim(P d 2m (X)), where in many applications N 2m card(X), obtaining a remarkable compression of the near optimal design. The theoretical foundation is a generalized version [15] of Tchakaloff Theorem [20] on positive quadratures, which asserts that for every measure on a compact set Ω ⊂ R d there exists an algebraic quadrature formula exact on P d n (Ω)), with positive weights, nodes in Ω and cardinality not exceeding N n = dim(P d n (Ω).…”
Section: Computing Near G-optimal Compressed Designsmentioning
confidence: 99%
“…In a recent paper [19], a connection has been studied between the statistical notion of G-optimal design and the approximation theoretic notion of admissible mesh for multivariate polynomial approximation, deeply studied in the last decade after Reference [13] (see, e.g., References [27,28] with the references therein). In particular, it has been shown that near G-optimal designs on admissible meshes of suitable cardinality have a G-efficiency on the whole d-cube that can be made convergent to 1.…”
Section: Hypercubes: Chebyshev Gridsmentioning
confidence: 99%
“…NURBS-shaped domains produced by CAGD algorithms play a central role in digital design and modelling processes. The capability of locating quasi-uniform or random sample points in such domains can be useful in a vast range of applications, for example within several meshfree bivariate approximation algorithms developed in the last twenty years, among which we may quote (without any pretence of completeness) kernel-based and partition-of-unity collocation methods [5,7], construction of algebraic cubature formulas [8,18,19] potentially useful for curved FEM/VEM elements [1,17], compressed MC/QMC integration [2,9], compressed polynomial regression [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…, φ N }. Then, using the notation K(x, y; w) := N i=1 φ i (x; w)φ i (y; w), (4) B(x; w) := K(x, x; w), (5) any D-optimal desig w * is also G-optimal, i.e., max x∈X B(x; w * ) = min…”
mentioning
confidence: 99%
“…There are several approaches to attack such a problem, treating X as a variable or a fixed parameter of the problem, which is chosen accordingly to certain heuristics as space filling techniques, grid exploration (see e.g., [8]), or minimal spanning tree. Recently, it has been shown that the use of polynomial admissible meshes gives precise quantitative estimates of the approximation intruduced in the discretization of the problem , i.e., when passing from X to X, see [5].…”
mentioning
confidence: 99%